Effects of Cutaneous Negative Pressure Application on Perforator Artery Flow in Healthy Volunteers: A Preliminary Study - Innocenti, Marco; Santini, Mariella; Dreassi, Emanuela; Martin, Robin; Melita, Dario; Colombini, Barbara; Innocenti, Alessandro (Journal of Reconstructive Microsurgery, 2019)
Background The creation of skin flaps based on small perforator vessels is an increasingly popular procedure nowadays; the optimization of their blood supply enhances surgical success. This study evaluates the effects on the flowmetries of 7 days' negative pressure application on the skin surface overlying the muscle fascia emergence of periumbilical perforators of the deep inferior epigastric artery (DIEA).Methods Ten volunteer participants were enrolled. In each subject, one periumbilical perforator of the DIEA was identified on each side of the abdomen using an eco-color-Doppler. One of them was used as the control group, while the other (the study group) underwent 80 mm Hg negative pressure for 7 days. The flowmetries of both perforators were measured before and after the application of negative pressure wound therapy.Results After the application of negative pressure, randomly applied on the skin surface over one of the two selected periumbilical perforators, an increase in the flowmetries was observed in both groups of perforators (2.74 cm/s; p < 0.0001). The relative flowmetry increase in the control group was 9.55% (2.735 cm/s), while in the study group it was 44.03% (8.748 cm/s).Conclusion The application of negative pressure system on the skin surface over the muscle fascia emergence of the selected periumbilical perforators showed an increase in flowmetry. Although this is a preliminary study, this simple and economical procedure before surgery could be usefully employed to increase the rate of success in microsurgical procedures.
Keywords: microsurgery; perforator flap; perforator; microsurgical procedures